Quantification of Physiologically Available Glycyrrhizin in Anti-Stress Herbal Formulations by Validated HPTLC Method - A. Siddiqui, Nasir; Alam, Perwez; Ali Khan, Azmat; Ahmad, Ateeque; J. Alrehaily, Adnan; M. Alanazi, Amer (Asian Journal of Chemistry, 2014)
In the present study a simple and novel high-performance thin-layer chromatography (HPTLC) method for quantitative determination of glycyrrhizin at stomach pH and its comparison with normal pH has been developed for marketed antistress liquorice root capsules and herbal tea. Chromatography was performed by using solvents including ethyl acetate:glacial acetic acid:methanol:water in proportion of 5:2:2:1, v/v/v/v as mobile phase. The developed plate was scanned and quantified densitometrically at absorption maxima 254 nm. The system was found to give compact spot for glycyrrhizin (Rf = 0.29 ± 0.001). The linearity relationship was described by the equation: Y = 2.103X + 25.289. Linearity range for glycyrrhizin was 100-1000 ng (r2 = 0.996). The amount of glycyrrhizin was estimated by comparing the peak area of standard and the same was present in the crude extract of antistress herbal formulations. The content of glycyrrhizin in 1 g of drug material at normal pH (i.e. 6.8) of methanol was estimated as 7.50 % w/w and 6.05 % w/w in a dose of sample liquorice root and herbal tea, respectively. At pH 2.58 the glycyrrhizin concentration declined to 5.43 % w/w and 3.28 % w/w in sample liquorice root and herbal tea, respectively. The method was validated for precision, accuracy, recovery, robustness, specificity, detection and quantification limits in accordance with ICH guidelines.